Pengaruh Profitabilitas, Leverage, Intensitas Aset Tetap Dan Pertumbuhan Penjualan Terhadap Penghindaran Pajak - Syamsiyah Laela Tunnisa; Indra Pahala; Muhammad Yusuf (Akuntansi, 2024)
This research aims to find out how profitability, leverage, fixed asset intensity and sales growth influence tax avoidance. The population used in this research is mining sector companies listed on the Indonesia Stock Exchange (BEI) in 2021-2022. Data collection uses documentation techniques obtained from the official website of the Indonesia Stock Exchange (BEI) via the link www.idx.co.id. Sample selection used purposive sampling technique. The samples obtained in accordance with the established criteria were 35 companies. The data analysis method uses panel data regression using Eviews 12 software. The results of hypothesis testing show that profitability has an effect on tax avoidance, while leverage, fixed asset intensity and sales growth have no effect on tax avoidance.